Emerging markers of inflammation and oxidative stress as potential predictors of coronary artery disease. (1st April 2023) - Tsirebolos, George; Tsoporis, James N.; Drosatos, Ioannis-Alexandros; Izhar, Shehla; Gkavogiannakis, Nikolaos; Sakadakis, Eleftherios; Triantafyllis, Andreas S.; Parker, Thomas G.; Rallidis, Loukianos S.; Rizos, Ioannis
Abstract: Background and aims: The multi-ligand receptor for advanced glycation end products (RAGE) and its ligands AGEs and S100/calgranulin proteins are important mediators of inflammation and oxidative stress whereas the soluble form of RAGE (sRAGE) by acting as a decoy and the antioxidant PARK7/DJ-1 exert antiatherogenic effects. We examined whether sRAGE and its ligands AGEs, S100A8/A9, S100B, S100A12 and DJ-1 are associated with the presence of angiographic coronary artery disease (CAD) in asymptomatic patients with and without diabetes. Methods and results: Plasma levels of RAGE ligands, sRAGE and DJ-1 were determined in 50 patients with angiographically proven CAD and in 50 age-matched healthy controls. In the whole cohort, lower levels of sRAGE and higher levels of interleukin-6 (IL-6), the RAGE ligands S100B, S100A12 and the AGEs/sRAGE ratio were associated with CAD. In patients without diabetes ( n  = 72), lower levels of sRAGE and DJ-1 and higher levels of IL-6 and AGEs/sRAGE ratio were associated with CAD. In multivariable analysis, AGEs/sRAGE ratio was an independent predictor of CAD both in the whole cohort ( p  = 0.034, OR = 1.247, [95%CI: 1.024, 1.0519]) and in the subgroup of patients without diabetes ( p  = 0.021, OR = 1.363, 95%CI [1.048, 1.771]) on top of established cardiovascular risk factors. Conclusion: Alterations in plasma RAGE axis inflammatory mediators are associated with atherosclerosis, and higher levels of AGEs/sRAGE ratio are independently associated with CAD in asymptomatic patients and may act as a novel biomarker for predicting CAD. DJ-1 emerges as promising marker of oxidative stress in CAD patients without diabetes, a finding that deserves further study. Highlights: In the cohort, CAD patients had higher IL-6, S100B, S100A12 and AGEs/sRAGE ratio and lower of sRAGE compared with controls. CAD patients without diabetes had higher IL-6, AGEs/sRAGE ratio and lower sRAGE and DJ-1 compared with controls. The soluble form of RAGE (sRAGE) by acting as a decoy and the antioxidant PARK7/DJ-1 may exert antiatherogenic effects. AGEs/sRAGE ratio is independently associated with CAD, on top of established cardiovascular risk factors.